Real-world effects of anti-dementia treatment on mortality in patients with Alzheimer´s dementia. Issue 45 (11th November 2022) - Nielsen, René Ernst; Grøntved, Simon; Lolk, Annette; Andersen, Kjeld; Valentin, Jan B.
Abstract : To examine the real-world effects of the cholinesterase inhibitors (AChEI) on all-cause mortality. A nationwide, retrospective cohort study. Participants were diagnosed with incident AD in Denmark from January 1, 2000 to December 31, 2011 with follow-up until December 31, 2012. A total of 36, 513 participants were included in the current study with 22, 063 deaths during 132, 426 person-years of follow-up. At baseline, patients not treated with AChEI (n = 28, 755 [9961 males (35%)]) had a mean age ± standard deviation (SD) of 80.33 ± 7.98 years (78.97 ± 8.26 for males and 81.04 ± 7.98 for females), as compared to 79.95 ± 7.67 (78.87 ± 7.61 for males and 80.61 ± 7.63 for females) in the group exposed at baseline. Patients treated with AChEI had a beneficial hazard ratio (HR) of 0.69, 95% confidence interval (CI) (0.67–0.71) for all-cause mortality as compared to patients not treated, with donepezil (HR 0.80, 95% CI [0.77–0.82]) and galantamine (HR 0.93, 95% CI [0.89–0.97]) having beneficial effects on mortality rate as compared to non-treatment, whereas rivastigmine (HR 0.99, 95% CI [0.95–1.03]) was associated with a mortality rate comparable to non-treatment with AChEI. Patients were primarily exposed to donepezil (65.8%) with rivastigmine (19.8%) and galantamine (14.4%) being used less often. These findings underscore the effect of AChEI on not only reducing speed of cognitive decline but also directly prolonging life, which could result in changes in treatment recommendation for when to stop treatment.